Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s13613-016-0162-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and features of acute kidney injury complicating hypoxic hepatitis at the medical intensive care unit

Abstract: BackgroundHypoxic hepatitis (HH) is a frequent and potentially life-threatening event typically occurring in critically ill patients as a consequence of hemodynamic impairment. While acute kidney injury (AKI) has been well described in patients with acute liver failure, incidence and outcome of AKI accompanying HH are unclear. The aim of this study was to assess incidence, clinical implications and outcome of AKI and renal replacement therapy (RRT) in critically ill patients with HH.MethodsA total of 1948 cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 32 publications
3
28
1
Order By: Relevance
“…Most cardiologists chose to stop the treatment in these particular situations. A recent study on 851 patients admitted to ICU, of which 87 presented IH/HH, showed that IH/HH had developed in 11% of those without statin therapy vs. 5% of subjects on statins at admission (26). These results need further validation in future studies.…”
Section: Treatment Principlesmentioning
confidence: 96%
See 1 more Smart Citation
“…Most cardiologists chose to stop the treatment in these particular situations. A recent study on 851 patients admitted to ICU, of which 87 presented IH/HH, showed that IH/HH had developed in 11% of those without statin therapy vs. 5% of subjects on statins at admission (26). These results need further validation in future studies.…”
Section: Treatment Principlesmentioning
confidence: 96%
“…In a recent study on 240 patients with IH/HH, 81% developed AKI, more than with half stage 3 AKI. In IH/HH patients, AKI correlated with underlying disease severity, especially shock, vasoactive drugs and elevated lactate level on admission (26).…”
Section: Outcome and Prognosismentioning
confidence: 99%
“…Although hyperammonemia is frequently observed in patients with HLI, the impact of ammonia‐lowering measures has not been assessed in this patient population so far. Initiation of RRT improved 28‐day survival in a large observational analysis of patients with HLI . Although mortality was high in patients with HLI and RRT, kidney function recovered in 71% of the ICU‐surviving patients with 1‐year survival rates of approximately 60%.…”
Section: Hypoxic Liver Injurymentioning
confidence: 98%
“…HLI is by far the most common cause of massive elevated aminotransferase levels in hospitalized patients . The prevalence of HLI ranges between 1% and 12% in ICU and may be even higher in patients with cardiogenic shock, in whom the prevalence was reported to be greater than 20% …”
Section: Hypoxic Liver Injurymentioning
confidence: 99%
See 1 more Smart Citation